Golongane Wong Kristen Kang Mardika: Misi Integral Kyai Sadrach dan Relevansinya Bagi Gereja Masa Kini - Kristian Kusumawardana (Sekolah Tinggi Teologi Bandung, 2024)
God situates the church in the midst of a world that is sinful and suffering, so that the church can proclaim and demonstrate the Gospel, so that more and more people will taste and enjoy a life of true peace. Kyai Sadrach and his community which was called Golongane Wong Kristen Kang Mardika was a church that God has brought to the land of Java, which proclaimed and demonstrated the Gospel, so that many Javanese people experienced its real impact. This article explores the integral mission ministry that they used and draws its relevance for the church today. The research method used is qualitative, with comprehensive literature study data collection techniques, analyzing data, and presenting it according to the topic and research objectives. The results of the study show that Kyai Sadrach and his community carried out integral mission: evangelism, educational mission, discipleship mission, social mission, economic mission, health mission, ecological mission, and cultural mission; which had a major impact on the growth of the Javanese church. Therefore, the church today must be a church that is missional, contextual, and virtuous, so that the presence of the church to bring the shalom of God's Kingdom to the world is truly felt by many people.